When do people exploit moral wiggle room?: an experimental analysis of information avoidance in a market setup - Momsen, Katharina; Ohndorf, Markus (Ecological economics, 2020)
We investigate if decision makers avoid information to exploit moral wiggle room in green market settings. We therefore implement a laboratory experiment in which subjects purchase products associated with externalities. In six between-subjects treatments, we alter the availability of information on the externalities, the price of revealing information as well as the nature of the externality, which could either affect another subject or change the amount spent by the experimenters on carbon offsets. We find that subjects do not strategically avoid information when revealing information is costless. When a very small cost of revealing information is introduced, their behavior depends on the relation between prices and externalities. In situations in which it is relatively cheap to have a large impact on the recipient's payoff, subjects avoid information in order to choose selfishly. For other parameterizations, subjects behave either honestly egoistically or altruistically.
Online veröffentlicht am 29. November 2019
Gesehen am 07.08.2023